Mirror-touch and ticker tape experiences in synesthesia - Chun, Charlotte A.; Hupé, Jean-Michel (Frontiers in Psychology, 2013)
A fundamental question in the field of synesthesia is whether it is associated with other cognitive phenomena. The current study examined synesthesia’s connections with phenomenal traits of mirror-touch and ticker tape experiences, as well as the representation of the three phenomena in the population, across gender and domain of work/study. Mirror-touch is the automatic, involuntary experience of tactile sensation on one's own body when others are being touched. For example, seeing another person’s arm being stroked can evoke physical touch sensation on one’s own arm. Ticker tape is the automatic visualization of spoken words or thoughts, such as a teleprompter. For example, when spoken to, a ticker taper might see mentally the spoken words displayed in front of his face or as coming out of the speaker’s mouth. To explore synesthesia’s associations with these phenomena, a diverse group (n=3,743) was systematically recruited from eight universities and one public museum in France to complete an online screening. Of the 1,017 eligible respondents, synesthetes (across all subtypes) reported higher rates of mirror-touch and ticker tape than non-synesthetes, suggesting that synesthesia is associated with these phenomenal traits. However effect size was small and we could not rule out that response bias influenced these associations. Mirror-touch and ticker tape were independent. No differences were found across gender or domain of work and study in prevalence of synesthesia, mirror-touch or ticker tape. The prevalence of ticker tape, unknown so far, was estimated at about 7%, an intermediate rate between estimates of grapheme-color (2 to 4%) and sequence-space synesthesia (9 to 14%). Within synesthesia, grapheme-personification, also called ordinal-linguistic personification was the most common subtype and was estimated around 12%. Co-occurences of the different types of synesthesia were higher than chance, though at the level of small effect sizes.